2022
DOI: 10.3991/ijet.v17i23.36619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Engagement and Learning Based on a Student Categorization using STACK, Exam Data, Key Informant Interviews, and Focus Group Discussions

Abstract: Abstract—Systems for Teaching and Assessment using Computer Algebra Kernel (STACK) is a computer-aided assessment plug-in for the Moodle learning management system that provides sophisticated tools for student assessment in mathematics and related disciplines, with emphasis on formative assessment. In the last four years, IDEMS international has supported the School of Mathematics at Maseno to integrate STACK and use it in the teaching, learning, and assessment of undergraduate students in nine courses. One of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Students' performance in online practice moderately correlated with their final UDSM examination results, this is very similar to the findings by Sangwin [7]. However, the result of online quizzes may mislead our decisionmaking, as some students do not work on their own [18,28]. Some mechanisms, such as, use of cameras, may be needed to ensure the security of the practice.…”
Section: (Feedback)supporting
confidence: 80%
See 1 more Smart Citation
“…Students' performance in online practice moderately correlated with their final UDSM examination results, this is very similar to the findings by Sangwin [7]. However, the result of online quizzes may mislead our decisionmaking, as some students do not work on their own [18,28]. Some mechanisms, such as, use of cameras, may be needed to ensure the security of the practice.…”
Section: (Feedback)supporting
confidence: 80%
“…In the region, STACK has got little attention. The work of Juma et al [18,19] reported the use of STACK at the University of Maseno for Calculus and Complex Analysis courses. In both cases, the authors only reported the behavior and performance of students.…”
Section: Introductionmentioning
confidence: 99%